Cultural management and government role - Edalat Nemati (Management Science Letters, 2012)
Culture plays an important role on human lives and it has been in four ancient civilizations of China, Iran, Egypt and Greece. The civilization achievements are normally categorized in two different groups of material and immaterial. Practical experience of the material, social objective is called as a civilization and the mental aspect of spiritual experiences, spiritual and personal is called culture. The purpose of this research is to find a framework for cross-cultural management. First, we define the cultural planning and we review the existing cultural examples in Iranian society and try to provide an overall analysis. The paper also investigates the role of government on creating adaptive culture within the society and explains that government must act as leadership in creating value added culture.